Jewish women in pre-state Israel : life history, politics, and culture - Kark, Ruth; Shilo, Margalit; Hasan-Rokem, Galit (HBI series on Jewish women., 2008)
A critical look at the history and culture of women of the Yishuv and a call for a new national discourse.